2007
DOI: 10.1021/bm0701088
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Poly(amidoamine) Dendrimers Terminated with Amino and Poly(ethylene glycol) Groups

Abstract: Poly(amidoamine) (PAMAM) dendrimer derivatives have been investigated for their biological applications, especially for delivery of drugs, including antimicrobial drugs to eukaryotic cells, but their effects on bacterial cells are largely unexplored. Herein we report that amino-terminated PAMAM dendrimers are highly toxic to the common Gram-negative pathogen Pseudomonas aeruginosa. The concentration that kills 50% of the bacteria (EC50) was in the range of approximately 0.9-1.5 microg/mL for the generation 5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
209
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(220 citation statements)
references
References 53 publications
7
209
2
2
Order By: Relevance
“…It has been reported that the antibacterial activity is related to the generation of the PAMAM-NH 2 (11,12). Our current results showed that G2.0-4.0 PAMAM-NH 2 had greater antibacterial activity than G1.0 PAMAM-NH 2 , whereas G2.0 PAMAM-NH 2 exhibited comparable or higher antibiotic activities than G3.0 and G4.0 PAMAM-NH 2 .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been reported that the antibacterial activity is related to the generation of the PAMAM-NH 2 (11,12). Our current results showed that G2.0-4.0 PAMAM-NH 2 had greater antibacterial activity than G1.0 PAMAM-NH 2 , whereas G2.0 PAMAM-NH 2 exhibited comparable or higher antibiotic activities than G3.0 and G4.0 PAMAM-NH 2 .…”
Section: Discussionsupporting
confidence: 49%
“…Among the PAMAM dendrimers harboring a variety of functional groups, amino-terminated PAMAM dendrimers (PAMAM-NH 2 ) show the strongest antibacterial activity. However, the previous studies primarily investigated the antibacterial activity of generation 3 or higher PAMAM-NH 2 dendrimers on limited bacterial strains in vitro (11,12). However, the higher-generation PAMAM-NH 2 dendrimers often show stronger cytotoxicity, which hinders further exploration of these compounds as antibacterial agents in vivo (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Calabretta et al [51] and Lopez et al [52] demonstrated concentration-dependent antibacterial properties of amine terminated PAMAM dendrimers (G3 and G5). With positively charged amine groups, they preferentially bound to bacterial membranes which have a higher charge density than eukaryotic cells.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…They are also suggested PAMAM dendrimers as the antimicrobial agents because of the fact that PEG-coated PAMAM derivatives exhibited low toxicity to human corneal epithelial cells (Calabretta et al, 2007). Epidemiologic studies performed in Europe countries report an increase in infectious diseases and bacterial resistance to antibiotics.…”
Section: Dendrimers As Antibacterial or Antimicrobial Agentsmentioning
confidence: 99%